Faktor-Faktor Yang Berhubungan dengan Kelengkapan Imunisasi Dasar pada Bayi di Puskesmas Ulee Kareng - Julinar Julinar; Isfanda Isfanda; Rayhatul Jinani (STIKes Ibnu Sina Ajibarang, 2023)
Factors Associated with Completeness of Basic Immunization for Infants at Ulee Kareng Health Center. Basic immunization is a program carried out to protect a person's body from diseases that can be prevented by immunization (PD3I) caused by viruses or bacteria, including tuberculosis, polio, diphtheria, pertussis, tetanus, hepatitis B, flu, measles and rubella. Based on data from the Directorate General of Disease Prevention and Management, the Indonesian Ministry of Health in 2018, ranks of Aceh Province are the lowest in basic immunization coverage, which is 70%. This study aims to determine the factors associated with completeness of immunization in infants with quantitative analytical methods with a cross sectional design approach (Cut Latitude). The study was conducted in March-July 2021 and obtained as many as 62 samples with the sampling method by accidental sampling. The results of this study indicate that there is a relationship between mother's knowledge and completeness of infant basic immunization with a p-value of 0.000, there is a relationship between mother's education and completeness of infant basic immunization with p-value of 0.000001, there is a relationship between mother's employment status and completeness of infant basic immunization p-value 0.003, and there is a relationship between family support and completeness of basic infant immunization with a p-value of 0.000. The distance to the place of immunization service does not have a relationship with the completeness of infant immunization with a p-value of 0.054. The efforts of the puskesmas in achieving immunization completeness were scored well by conducting an assessment of planning, implementation and assessment activities using a questionnaire containing 5 questions on planning, 5 questions on implementation and 5 questions on assessment. Based on the results of this study, it can be concluded that the level of knowledge, education, employment status, and family support has a relationship with the status of completeness of infant immunization. The distance to the place of immunization service does not have a relationship with the infant's immunization status. The researcher's suggestion is to do research with a larger sample and add various other variables that have a relationship with the infant's immunization status.